2018
DOI: 10.1177/0046958018778902
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Home Implementation of Health Information Technology: Review of the Literature Finds Inadequate Investment in Preparation, Infrastructure, and Training

Abstract: Health information technology (HIT) is increasingly adopted by nursing homes to improve safety, quality of care, and staff productivity. We examined processes of HIT implementation in nursing homes, impact on the nursing home workforce, and related evidence on quality of care. We conducted a literature review that yielded 46 research articles on nursing homes’ implementation of HIT. To provide additional contemporary context to our findings from the literature review, we also conducted semistructured interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 48 publications
2
76
2
Order By: Relevance
“…The context varied in our sample with for example different nursing tasks in home care and nursing homes, differences in size, location, and distance to hospitals. We also found variation in access to reliable networks and communication with GPs in home care and nursing homes that sometimes challenged the staffs and managers work, in line with previous research [19]. However, our results are consistent with previous research showing that one of the greatest leadership challenge is to prepare and facilitate processes for organizational change [20,21].…”
Section: The Contextual Impact On Quality and Safety Worksupporting
confidence: 91%
“…The context varied in our sample with for example different nursing tasks in home care and nursing homes, differences in size, location, and distance to hospitals. We also found variation in access to reliable networks and communication with GPs in home care and nursing homes that sometimes challenged the staffs and managers work, in line with previous research [19]. However, our results are consistent with previous research showing that one of the greatest leadership challenge is to prepare and facilitate processes for organizational change [20,21].…”
Section: The Contextual Impact On Quality and Safety Worksupporting
confidence: 91%
“…The managers' level of engagement and active involvement in the implementation of WNCSs appears to be higher in this study than in previous studies of health information technology implementation in residential care facilities, which reported a lack of involvement as well as lack of systematic planning and decision-making from managers [29,31,32,35]. The care providers' evaluation of the managers' efforts supported the effect of an implementation strategy adopted by all care facilities; that the unit managers had learned to use the WNCS and taken an essential role for driving the implementation [57].…”
Section: Motivating Managerscontrasting
confidence: 80%
“…This complexity should be accounted for and attended to in order to facilitate successful implementation, and develop new knowledge and practice. Within this complexity, factors that affect implementation processes include the physical environment and infrastructure, availability of time and resources, availability of staff training, availability of support, receptiveness of organizational culture, involvement of all stakeholders, demonstrable benefits of the change and empowering leadership [34][35][36][37][38][39].…”
Section: Implementation Of Transformative Digital Health Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In their literature review, combined with qualitative findings, Ko, Wagner, and Spetz () found that NHs faced many challenges in technology implementation. For example, many did not use a systematic implementation process or lacked the appropriate infrastructure to support the use of technology.…”
Section: Introductionmentioning
confidence: 99%